2017
DOI: 10.1109/jstsp.2017.2740167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Evaluation of Light Field Image Coding Approaches

Abstract: Abstract-The recent advances in light field imaging, supported among others by the introduction of commercially available cameras e.g. Lytro or Raytrix, are changing the ways in which visual content is captured and processed. Efficient storage and delivery systems for light field images must rely on compression algorithms. Several methods to compress light field images have been proposed recently. However, in-depth evaluations of compression algorithms have rarely been reported. This paper aims at evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 35 publications
0
51
0
2
Order By: Relevance
“…The compression rates attained using VQ are around 10:1 to 20:1. A survey of compression schemes for LFI is presented in Viola et al [Viola et al 2017].…”
Section: Light Field Compressionmentioning
confidence: 99%
“…The compression rates attained using VQ are around 10:1 to 20:1. A survey of compression schemes for LFI is presented in Viola et al [Viola et al 2017].…”
Section: Light Field Compressionmentioning
confidence: 99%
“…The methodology was successfully used to evaluate how different approaches in LF compression can affect the visual quality of the content. 16 Moreover, its validity was tested against a standard passive methodology, which allowed the users to see a pre-recorded animation of the LF content, without any possibility to interact with it. …”
Section: 13mentioning
confidence: 99%
“…A new interactive assessment methodology was already introduced by the authors, 15 and it was successfully used in evaluation of quality of LF contents in presence of compression artefacts. 16 However, it was shown that the interactive methodology had less discriminative power when compared to a passive approach, and leads in general to larger confidence intervals.…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…In order to store, transmit, and render LFI, it is important to develop good compression algorithms. Different schemes have been proposed for compressing LFI, as surveyed in [Viola et al 2017]. The majority of these methods provide high compression rates, like standard 2D image compression methods, but they require decoding all the LFI samples into memory before rendering.…”
Section: Introductionmentioning
confidence: 99%